LINGUOCULTURAL FACTORS OF TERMS RELATED TO COUNTRY STUDIES IN ENGLISH AND UZBEKISTAN - Tairova Mahfuza Abdusattarovna (Innovate Conferences, 2025)
This article presents an analysis of the linguocultural factors of terms related to country studies through examples.
Keywords: linguoculturology, country studies, term, factors, linguistics, feature.